Un type d’étayage en rééducation orthophonique: émergence et développement de stratégies d’appropriation ou de réappropriation de l’écrit - Lederle, Emmanuelle (Travaux neuchâtelois de linguistique, 2003)
As a speech and language therapist dealing with children in difficulties with written language, I chose to reflect upon what children know or may tell about the way they operate in that matter. Works carried out by J. Piaget, L.S. Vygotski, J.S. Bruner, about the development and learning in children in various areas of research (development psychology, social psychology of cognitive development) enabled me to build the following hypothesis: interactive strategies used by an «expert-adult» may allow the birth and implementation, with the learner, of cognitive and linguistic procedures. These procedures lead to appropriation or re-appropriation of the written language. I consider speech and language therapy for written language disorders, as a particular verbal interaction situation, enabling the pointing out of strategies across individuals’ interactions: scaffolding strategies (planned or improvised) on the adult side, cognitive, metacognitive and socioaffective strategies on the children side. In this article I will describe the children’s «reactions».